Influence of Commercial Insurance Purchase on the Health Status of Chinese Residents - Xu, Bao-Chang; Li, Xiu-Juan; Gao, Meng-Yao (Frontiers in Public Health, 2021)
Under the context of rapid economic and social development and growing demands for a better life, Chinese residents have been increasingly concerned with their health status and issues. In this paper, the internal relations between residents’ purchase of commercial insurance and their health status are analyzed and studied with a polytomous logit model based on the data of Chinese General Social Survey (CGSS) in 2015. According to the research result, purchase of commercial insurance significantly improved residents’ health status, with an improving effect for rural residents apparently better than that among urban residents. Besides, purchase of commercial insurance can promote residents’ health status by increasing their household income. This research will provide effective reference for the innovative development and medical reform of China’s commercial insurance in the future, which is theoretically and practically significant to the implementation of the Healthy China Strategy.